2015
DOI: 10.1016/j.ijhcs.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The adaptation of visual search to utility, ecology and design

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 88 publications
0
8
0
1
Order By: Relevance
“…[ 18 ]) and to assess in an objective way whether participants achieved the best scores they could. This provides support for the notion that rational agents optimize their performance so as to maximize their payoff [ 18 , 35 , 53 56 , 68 ]. We showed that incentives have consequences for the strategies that are selected for interleaving attention and for performance on each of the individual task (e.g., total time spent typing, and maximum deviation of a cursor).…”
Section: Discussionmentioning
confidence: 79%
“…[ 18 ]) and to assess in an objective way whether participants achieved the best scores they could. This provides support for the notion that rational agents optimize their performance so as to maximize their payoff [ 18 , 35 , 53 56 , 68 ]. We showed that incentives have consequences for the strategies that are selected for interleaving attention and for performance on each of the individual task (e.g., total time spent typing, and maximum deviation of a cursor).…”
Section: Discussionmentioning
confidence: 79%
“…Computational rational agents have been used to model a number of phenomena in HCI (Payne & Howes, 2013). Applications relevant to this paper include menu interaction (Chen et al, 2015), visual search (Hayhoe & Ballard, 2014;Myers, Lewis, & Howes, 2013;Nunez-Varela & Wyatt, 2013;Tseng & Howes, 2015), and decision-making (Chen, Starke, Baber, & Howes, 2017).…”
Section: Example 2: Computational Rationalitymentioning
confidence: 99%
“…Particularly, researchers call for more extensive usage of mathematical cognitive models that are currently "under-exploited" in HCI [4] (p. 2), and [2]. Today's trend in such models is consideration of utility for subjects [4] or costbenefit trade-offs [5], e.g., the ones optimizing the "expenditure" of perceptual-motor plus cognitive resources [6]. Among other things, they can predict the time spent by users in tasks of various difficulties so that the verification of UIs can be carried out without studies with the actual users [2,4].…”
Section: Introductionmentioning
confidence: 99%